Dinuclear gold(i) complexes with N-phosphanyl, N-heterocyclic carbene ligands: synthetic strategies, luminescence properties and anticancer activity. Issue 38 (10th September 2021) - Trevisan, Gianmarco; Vitali, Valentina; Tubaro, Cristina; Graiff, Claudia; Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiia N.; Kostyuk, Aleksandr; Mauceri, Matteo; Rizzolio, Flavio; Accorsi, Gianluca; Biffis, Andrea
Abstract : Novel dinuclear Au complexes with NHCP ligands have been prepared, exhibiting tuneable luminescence properties and in vitro anticancer activity, which were found to depend on complex charge and ligand substitution. Abstract : A small library of dinuclear gold(i ) complexes with the title ligands has been prepared, encompassing neutral, mono- and dicationic complexes. The luminescence properties of the complexes in the solid state have been evaluated, and it turns out that neutral and monocationic complexes not presenting a rigid metallamacrocyclic structure can exhibit rather strong emissions that extend towards the red region of the visible spectrum. The in vitro anticancer activity of the complexes has been also preliminarly evaluated; cytotoxicity seems to correlate with complex lipophilicity, whereas selectivity towards cancer cells can be apparently enhanced upon a judicious choice of the ligands.